Designs within disorder : Franklin D. Roosevelt, the economists, and the shaping of American economic policy, 1933 - 1945 - Barber, William J. (Historical perspectives on modern economics, 1996)
More than any of his predecessors in the White House, Franklin D. Roosevelt drew heavily on the thinking of economists as he sought to combat the Great Depression, to mobilize the American economy for war, and to chart a new order for the postwar world. Designs within Disorder is an inquiry into how divergent analytic perspectives competed for official favor and how the President chose among them when formulating economic policies. During the Roosevelt years, two "revolutions" were underway simultaneously. One of them involved a fundamental restructuring of the American economy and of the role government was to play in it. A second was an intellectual "revolution," which engaged economists in reconceptualizing the nature of their discipline. Most of the programmatic initiatives Roosevelt put in place displayed a remarkable staying power for over a half century.